2019
DOI: 10.4018/ijicte.2019100101
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Learning Outcomes in an Undergraduate IT Project Management Course

Abstract: Achieving higher order learning outcomes may be normal in developed country higher-education institutions, but it may not so for most of those in developing countries with resource poverty which manifests in high student-teacher ratios for instance. Lecturers in developing countries tend to use less student-centered teaching methods which hamper the achievement of higher order learning outcomes. Unfortunately, this issue has been ignored in the general information systems education literature. This article the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Literature also reported that academicians in developing countries are adopting a teaching approach that is less student-centred, thus hindering the integration of HOTS in the classroom [18]. Budu [18] also emphasised and encouraged academicians to adopt appropriate teaching methods that can cultivate HOTS among learners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature also reported that academicians in developing countries are adopting a teaching approach that is less student-centred, thus hindering the integration of HOTS in the classroom [18]. Budu [18] also emphasised and encouraged academicians to adopt appropriate teaching methods that can cultivate HOTS among learners.…”
Section: Literature Reviewmentioning
confidence: 99%